Universal health coverage anchored in the right to health - Ooms, Gorik; Brolan, Claire; Eggermont, Natalie; Eide, Asbjørn; Flores, Walter; Forman, Lisa; Friedman, Eric A; Gebauer, Thomas; Gostin, Lawrence O; Hill, Peter S; Hussain, Sameera; McKee, Martin; et al. (© 2013 Bulletin of the World Health Organization, 2017)
This editorial was published in the Bulletin of the World Health Organization [© 2013 Bulletin of the World Health Organization] and the definite version is available at: http://www.who.int/bulletin/volumes/91/1/12-115808/en/